The mediating role of youth’s self-representations in associations between adverse family experiences and externalizing behaviour. - Silva, C. S.; Calheiros, M. M. (XVth Biennial Conference of the European Association for Research on Adolescence, 2016)
The research gap about the mediating role of youths’ self-representations in associations between adverse family experiences and their externalizing behavior will be addressed in two studies. In study 1, we analyzed self-representations as mediators between interparental conflict and youth’s externalizing behavior in a normative sample of 229 adolescents, 10-18 years old, who reported on interparental conflict and self-representations. Homeroom teachers reported on externalizing behavior. Results showed significant mediation effects of instrumental, social and physical-appearance self-representations in associations between interparental conflict and externalizing behavior. In study 2, self-representations will be analyzed as mediators between maltreating parents’ appraisals and youth’s externalizing behavior, controlling for maltreatment. Participants are 214 youths, 6-16 years old, referred to children/youth protection committees, and their parents. The committees’ professionals reported on maltreatment; youths reported on self-representations; and parents reported on externalizing behavior. Data will be analyzed with conditional process analyses. Implications for research and practice will be discussed.